Efeito da variação da regulagem no perfil transversal de aplicação com distribuidores centrífugos - Farret, Isaias Salin (2005)
Centrifugal broadcaster spreaders are equipments that revolutionized the application technology application of solid material in agriculture, for presenting a great field capacity for operational field and being able to apply a large range of application rate. However, this equipment presents some inconveniences, such as the difficulty in applying the material evenly in the width used for a specific work, even when adjusting is a relatively simple task. Moreover, another problem is its behaviour variability according to the characteristics of the product that is used and the application conditions. The objective of this work was to compare treatments regarding operational adjustments in order to balance and uniform the transversal pattern of distribution, with a higher operational field capacity, for different solid products. The machine evaluated was a centrifugal broadcaster for solid material equipped with two spinning disks. The study proposal is to investigate the effect of the incomplete combination between the product type, the opening of the hopper metering system and the distribution disks impellers position. Results showed that the medium and high speeds of the conveying chain for lime distribution and the low speed for oat distribution gave a large and sufficient range of application rate by varying the opening of the metering device. According to the analysed conditions, a combination of opening position 15, impellers radial position, effective width of 10 meters and alternate application system, presented the best uniformity of lime distribution. For the oat, on the other hand, the best uniformity of distribution was reached when combining opening position 1, impellers in radial position, effective width of 10 meters and alternate application system. I increasing the flow and advancing the impellers position gave a higher field capacity. That was due to the possibility of a larger effective width as well as a higher travel speed for both lime and oat, thus preserving the transversal distribution uniformity. The maximum widths recommended are 13.5 meters for lime and for oat application.